Interaction between the level of immunoglobulins and number of somatic cells as a factor shaping the immunomodulating properties of colostrum - Kamila Puppel (Nature Portfolio, 2021)
Abstract The aim of this study was to investigate the association between immunoglobulins and SCC as a factor in shaping the content of the immunostimulatory components of colostrum. Seventy-eight multiparous Polish Holstein–Friesian cows were selected for the experiment. Colostrum samples were collected immediately after calving (up to a max. of 2 h). The cows were divided into groups according to the following levels: Immunoglobulins (IG class)—(IG1) over 50 g/L, (IG2) up to 50 g/L; SCC class—(SCC1) up to 400 000/ml, (SCC2) 400–800 000/ml, (SCC3) over 800 000/ml. Colostrum assigned to the IG1 SCC1 group had a statistically significant higher (p ≤ 0.01) concentration of both whey proteins and fatty acids compared to the IG1 SCC2 and SCC3 groups. The concentration of IgG, IgM, and IgA was shown to be higher in IG1 SCC1 than IG2 SCC3 by 226%, 149%, and 115%, respectively. The concentration of lactoferrin was shown to be higher in IG1 SCC1 than IG2 SCC3 by 149%. The determination of colostrum quality based on the concentration of immunoglobulins in the colostrum may not be sufficient because serum IgG concentrations at birth show a linear increase relative to colostrum SCC. A breakdown of colostrum into quality classes, taking into account the level of SCC, should therefore be introduced.